Свети Константин Кавасила како струмички епископ - Nedeski, Viktor (Завод за заштита на спомениците на култура и музеј - Струмица, 2017)
St. Constantine Cabasilas was really eminent archipriest of the Ohrid Archbishopric, but due to historical circumstances that followed shortly after his primacy, today we have partial and scarce data of his life and work. As a child of the famous race Cabasilas, Constantine had the opportunity to obtain good education, information that can be seen from its hymnographic works, but the wide range of his knowledge is witnessed by his questions addressed to several of his contemporaries. For the irst time we ind data about Saint Constantine Cabasilas as bishop of Strumica in 1220 and by this stage of his life the most important are his hymnographic works about the Holy Fifteen Tiberiopolis Martyrs – on whose cult revival he actively worked. His irst correspondence with the Archbishop of Ohrid Demetrius Homatian dates from the period of his duty as a bishop in Strumica. This correspondence is an important source, especially in the area of the church law but it is also an indicator of the problems that he faced as a bishop in the Strumica Diocese.